2013
DOI: 10.1002/adom.201300152
|View full text |Cite
|
Sign up to set email alerts
|

Is There Real Upconversion Photoluminescence from Graphene Quantum Dots?

Abstract: Figure 1. TEM images of GO (a) and GQDs (b). The inset of (b) shows the size distribution of GQDs with a probable size of 8.3 nm. wileyonlinelibrary.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 34 publications
3
81
2
1
Order By: Relevance
“…Considering second-order diffraction light (λ/2) is always present in the selected excitation light (λ) due to limitation of diffraction gratings used in the monochromators of the spectrofluorimeter, the so-called UCL should be not real UCL but normal luminescence excited by the second-order diffraction light of wavelength λ/2. Gan and coworkers provided new evidences to support the conclusion of Tan [207]. The time resolved PL measurement of the CDs synthesized by hydrothermally treating GO was performed.…”
Section: Upconversion Luminescencementioning
confidence: 88%
See 1 more Smart Citation
“…Considering second-order diffraction light (λ/2) is always present in the selected excitation light (λ) due to limitation of diffraction gratings used in the monochromators of the spectrofluorimeter, the so-called UCL should be not real UCL but normal luminescence excited by the second-order diffraction light of wavelength λ/2. Gan and coworkers provided new evidences to support the conclusion of Tan [207]. The time resolved PL measurement of the CDs synthesized by hydrothermally treating GO was performed.…”
Section: Upconversion Luminescencementioning
confidence: 88%
“…23 a Emission spectra excited at 400 nm (black), 800 nm without (red) and with (blue) a 420 nm cutoff filter in the excitation channel [206]. b Time resolved PL monitored at 460 nm emission excited by the selected light of 320 (circles) and 640 nm (squares) [207] excitation source and the sample in order to eliminate the light at 400 nm (800/2) from light source), nearly no luminescence could be detected when excited at 800 nm. Considering second-order diffraction light (λ/2) is always present in the selected excitation light (λ) due to limitation of diffraction gratings used in the monochromators of the spectrofluorimeter, the so-called UCL should be not real UCL but normal luminescence excited by the second-order diffraction light of wavelength λ/2.…”
Section: Upconversion Luminescencementioning
confidence: 99%
“…Later, several other groups observed similar UCPL from CQDs prepared via different synthetic routes. For instance, Gan et al [39] demonstrated that blue light centered…”
Section: Up-conversion Photoluminescence (Ucpl)mentioning
confidence: 99%
“…Nevertheless, some researchers argued that the up-conversion PL observed might be artificial, rather than from GQDs themselves. 22,23 It is demonstrated that the second-order diffraction light of Xenon lamp at l/2 coexisting in the excitation light actually may contribute to the observed up-conversion PL. In this point, the second order grating diffraction would be ruled out when considering the up-conversion phenomenon.…”
Section: Properties Of Gqdsmentioning
confidence: 98%